The Application Research of Aerocraft Simulation System for Speediness prototype and Integrative Modeling - Chao Yun; Xiao-min LI (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
For solve the problem of flight simulation system accurately modeling, speediness and high efficiency implement. It bring forward flight simulation system of aerocraft speediness and integrative modeling method based on Aerosim/RTW. Compare with traditional development method for flight simulation system, the method who based on Aerosim/RTW could implement speediness prototype and integrative process which from digital simulation model establishing to system implement. Lastly the simulation results showed that: this technique based on Aerosim/RTW could achieve speediness prototype and integrative construct for aerocraft dynamic flight simulation system and give birth to remote sensing of flight data flow. The technology have simpleness, conveniency and high efficiency characteristic in the course of constructing for the flight simulation system of aerocraft. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3885